Searching for a new Kenya politics and social media on the streets of Mombasa - Diepeveen, Stephanie 1986- (University of Cambridge, Cambridge University Press, 2021)
Searching for a New Kenya analyses public discussion in urban Kenya, focusing on the gatherings of citizens, both in-person and online, where people discuss issues of common concern to shed light on the role public discussion plays in politics and how social media affects political movements. Through rich ethnographic study of politics on the ground and online in Mombasa, Stephanie Diepeveen brings a fresh perspective on the wider challenges and dynamics of negotiating political narratives across protracted historical debates and changing digital media. Based on a critical revision of Hannah Arendt's ideas about action and power, this study explores the different dynamics of public talk in practice. It contributes to wider debates about the place and limitations of the Western canon in relation to the study of politics elsewhere, while also offering a nuanced view of why and how certain terms of debate persist in Kenya, and where the potential for change lies for public talk across changing media
Title from publisher's bibliographic system (viewed on 21 May 2021)
Keywords: Social media / Kenya / Mombasa; Zivilgesellschaft; Social Media; Politische Beteiligung; Kenya / Politics and government; Kenya / Economic conditions; Kenia